Combatting the Epidemic of E-cigarette Use and Vaping among Students and Transitional-age Youth - Domenico, Lisa; DeRemer, Christina E.; Nichols, Kathy L.; Campbell, Christopher; Moreau, Jacquelyn R.; Childs, Gail S.; Merlo, Lisa J. (Current Psychopharmacology, 2021)
Background: Over the past decade, the use of electronic nicotine delivery system (ENDS) devices such as e-cigarettes has increased dramatically, particularly among students and other transitional- age youth. Societal norms and the variety of ENDS devices available have also evolved dramatically in recent years. Objective: This article provides a comprehensive review and synthesis of contemporary literature, as it relates to ENDS use among transitional-age youth. Methods: Over 125 peer-reviewed studies, literature syntheses, legal reports and contemporary media works focused on ENDS use and vaping were reviewed. Results: Marketing strategies for ENDS devices have primarily targeted teens and young adults. Though ENDS devices are advertised as a safer alternative to cigarettes, accumulating data demonstrate significant health risks and consequences associated with use. The long-term health effects remain largely unknown; however, detrimental acute effects are apparent. Furthermore, rather than aiding in tobacco cessation efforts, the use of ENDS by transitional-age youth is correlated with the increased use of conventional tobacco products and other substances of abuse. Students appear to be ill-informed regarding the dangers of using ENDS products. Conclusion: Given the rapid increase in ENDS users each year, and accumulating concerns about health risks associated with use, university student health services must be prepared to address this growing problem. As clinical practice guidelines do not yet exist to encourage ENDS-product cessation, the use of the evidence-based strategies developed for tobacco cessation is advised. More research is needed to determine the most effective methods to prevent the initiation of ENDS use within this population.
Keywords: electronic nicotine delivery systems